Characterizations of Some Regularities in Ordered Ternary Semigroups in Terms of Fuzzy Subsets - Lekkoksung, Nareupanat; Sanpan, Hataikhan; Lekkoksung, Somsak (Communications in Mathematics and Applications, 2021)
Characterizations of some classes of ordered ternary semigroups; left (resp., right) lightly regular and generalized regular are given in terms of fuzzy left ideals, fuzzy right ideals, fuzzy lateral ideals, and fuzzy ideals of ordered ternary semigroups.
Keywords: Fuzzy left ideal; Fuzzy lateral ideal; Fuzzy right ideal; Ordered ternary semigroup